HUBUNGAN KONSUMSI MAKANAN DENGAN KUALITAS ASI DI DAERAH PENAMBANGAN EMAS - Aryani Sudja (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2012)
reast milk is the most perfect food for babies, which provides high-value nutrients that required for growth, development and immunity. Healthy milk contains nutrients and does not contain contaminants (heavy metals), such as mercury. The use of mercury (Hg) in the process of separating gold in traditional gold mining through process of amalgamation in long time will result in mercury wastes that may pollute the river water, groundwater and soil. Mercury that pollutes the land will remain in the ground and then seep into groundwater or flow into streams when it rains. Mercury will be absorbed by plant roots and will mount up in fruits and leaves (vegetables), while the mercury in the river or pond water will accumulate in the body of the fish. People who live in gold mining areas, including nursing mothers who consume such food will indirectly consume mercury and it will accumulates in the body for a long time as well. This condition will cause health problems throuhout their lives. Mercury in body fluids, including in breast milk, will affect the protein content of · breast · milk · and inhibit enzyme activity. The aim of this study is to, identify the relationship between food consumption in the areas of gold mining with the quality (me'rcury and protein content) of breast milk. Subjects were pregnant women who live in gold mining areas in the District of Cineam Tasikmalaya Regency. Data collected include the food consumption of nursing mothers, protein and mercury in breast milk, and mercury in food. Food consumption data is collected by interview, whereas protein and mercury in breast milk and mercury in food obtained by using Atomic Absorption Spectrophotometer method (AAS). Statistical analysis used Spearman correlation between variables. The results showed average mercury content in some foodstuffs ranged from 0.01572 ppm -0.31086 ppm, the average daily intake of mercury is 25.81 µg, the average protein in breast milk is 1. 758 g/100 ml and the average mercury in breast milk is 1.011 ppb. Results of analysis among variables showed a significant correlation between the consumption of food (intake of mercury) a day with the content of mercury in breast milk (p = 0.043, r = 0.365) and mercury content in human milk with protein content in milk (p = 0.001, r =- 0.567).